A Nanostructuring Method to Decouple Electrical and Thermal Transport through the Formation of Electrically Triggered Conductive Nanofilaments. Issue 28 (28th May 2018) - Durán Retamal, José Ramón; Kang, Chen‐Fang; Lien, Der‐Hsien; Kuo, Wei‐Cheng; Juang, Zhen‐Yu; Tsai, Meng‐Lin; Ho, Chih‐Hsiang; Juang, Jenh‐Yih; Hsiao, Vincent K. S.; Chu, Ying‐Hao; Li, Lain‐Jong; Wu, Yue; et al.
Abstract: Transforming thermal energy into electric energy and vice versa needs the decoupling of electrical transport from thermal transport. An innovative strategy is proposed by forming/disrupting electrically triggered conductive nanofilaments within semiconducting thin films to switch thermoelectric properties between two states without further material modification and manufacturing processes. It can also controllably adjust the degree of decoupling, providing a potential resolution and performance adjustability for heat/coldness control or power consumption reduction on demand. Abstract : A nanostructuring method based on the formation/disruption of conductive nanofilaments (CNFs) within a thin film is developed via electrical stress. The formation of the CNFs enables metallic nanoscale percolation paths for electrical and thermal carrier transport, while the disruption of the CNFs breaks the direct connectivity for both types of transport. Therefore, electrical and thermal conductivities are synergistically optimized between two switchable thermoelectric states.